BAHAYA POLITIK UANG PADA PENYELENGGARAAN PEMILIHAN KEPALA DAERAH : (Pendidikan Politik Masyarakat Desa Wanagading, Kecamatan Bolano Lambunu, Kabupaten Parigi Moutong Dalam Rangka Menyongsong Pemilihan Kepala Daerah Tahun 2024) - Irwan Waris; Ani Susanti; Muhammad Afandi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This Community Service activity is titled "The Dangers of Vote-Buying Practices in Local Elections." The initiative was based on the findings of research conducted by Irwan Waris, entitled Vote-Buying in the 2020 Regional Elections in Central Sulawesi. The study revealed that vote-buying practices continued during the campaign period and in the lead-up to the local election day in Palu City and Parigi Moutong Regency. Similar political activities also occurred in other regions. Theoretically and empirically, these vote-buying practices influence the quality of elected leaders, which ultimately harms the public. Elected regional leaders may not genuinely focus on regional development and the welfare of the people .The objectives of this activity include providing knowledge and understanding to the public about the dangers of vote-buying in local elections and preventing or at least minimizing its occurrence. This activity will be carried out in Wanagading Village, Bolano Lambunu District, Parigi Moutong Regency. The community service activity will take the form of public education sessions held through meetings or lectures, involving eligible voters in Wanagading Village, Bolano Lambunu District, Parigi Moutong Regency, over the course of one day. Approximately 40 community leaders are expected to participate in the activity, which will be conducted in stages: preparation, participant selection, implementation, and reporting. It is hoped that participants in this activity will apply the knowledge gained and serve as inspirators and resource persons, reminding other community members about the dangers of vote-buying in local elections. The outcome of this community service activity will be a scholarly article published in the Journal of Community Service, LPPM, Tadulako University.